Rancang Bangun E-Learning SMK Negeri 2 Padang - Tsaqif Luthfan,; Titi Sriwahyuni, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The digital learning process at SMK Negeri 2 Padang has not been optimally managed due to the lack of an e-learning system. Materials and assignments are still managed through platforms like WhatsApp, making learning data difficult to document and the assessment process less efficient. This research aims to design and build a web-based e-learning system that can assist teachers, students, and the school in managing learning activities digitally and in an integrated manner. The system was developed using the Waterfall model, encompassing requirements, UML design, implementation, and testing. The application was built using the Laravel and Laravel Filament frameworks, using MySQL as the database and Tailwind CSS for the user interface. Black Box Testing demonstrated that all features functioned as required. The system supports multi-level logins for admins, teachers, students, and curriculum representatives, each with their respective access rights. The research results indicate that this e-learning system can help make the learning process more efficient, structured, and documented through features such as uploading materials, submitting assignments, quizzes, and a repository across grade levels.